2014
DOI: 10.1111/pace.12383
|View full text |Cite
|
Sign up to set email alerts
|

Association of Time of Occurrence of Electrical Heart Storms with Environmental Physical Activity

Abstract: These data extend earlier findings on the association of the timing of cardiac events and space weather parameters to the most dangerous form of cardiac arrhythmia-electric storms. Further studies are needed to delineate the pathogenetic mechanism underlying this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…GMA has been observed to be positively associated with arterial blood pressure [6], some blood coagulation parameters [7], the marker of inflammation, C-reactive protein level [8], and it is negatively associated with heart rate variability [1,9] and melatonin concentration [10]. It has been indicated that low GMA was associated with an increase in electrical heart instability [11,12]. These effects of GMA have been explained by the effects of the magnetic field on ions and protons in the human body [2,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…GMA has been observed to be positively associated with arterial blood pressure [6], some blood coagulation parameters [7], the marker of inflammation, C-reactive protein level [8], and it is negatively associated with heart rate variability [1,9] and melatonin concentration [10]. It has been indicated that low GMA was associated with an increase in electrical heart instability [11,12]. These effects of GMA have been explained by the effects of the magnetic field on ions and protons in the human body [2,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…On Earth, biological systems are also subject to the naturally varying geomagnetic field (GMF) (Dubrov, 1978). This variation in geomagnetic disturbance has been shown to impact not only animal behavior (Beischer, 1971;Zamoshchina et al, 2012), but also medically relevant phenomena such as ciliary motion (Sandoze, Svanidze, & Didimova, 1995), stem cell function (Mo, Liu, Bartlett, & He, 2014), cardiovascular regulation (Cornelissen et al, 2001;Feigin et al, 2014;Gmitrov & Gmitrova, 2004;Stoupel, 2006;Stoupel et al, 2014), the autonomic nervous system (Baevsky, Petrov, & Chernikova, 1998), memory (Wang, Xu, Li, Li, & Jiang, 2003;Xiao, Wang, Xu, Jiang, & Li, 2009;Zhang et al, 2004), and the interactions between neurons (Shibib, Brock, & Gosztony, 1987). Magnetic field reversals may even have placed selective pressures on organisms that have contributed to subsequent extinction (Hays, 1971;Plotnick, 1980) and morphological change (Harrison & Funnel, 1964), and planaria have specifically been shown to be sensitive to weak magnetic fields (Brown, 1962b.…”
mentioning
confidence: 99%